The N terminus of cGAS de‐oligomerizes the cGAS:DNA complex and lifts the DNA size restriction of core‐cGAS activity. Issue 6 (7th March 2017) - Lee, Arum; Park, Eun‐Byeol; Lee, Janghyun; Choi, Byong‐Seok; Kang, Suk‐Jo
Abstract : Cyclic GMP‐AMP synthase (cGAS) is a DNA‐sensing enzyme in the innate immune system. Recent studies using core‐cGAS lacking the N terminus investigated the mechanism for binding of double‐stranded (ds) DNA and synthesis of 2′, 3′‐cyclic GMP‐AMP (cGAMP), a secondary messenger that ultimately induces type I interferons. However, the function of the N terminus of cGAS remains largely unknown. Here, we found that the N terminus enhanced the activity of core‐cGAS in vivo . Importantly, the catalytic activity of core‐cGAS decreased as the length of double‐stranded DNA (dsDNA) increased, but the diminished activity was restored by addition of the N terminus. Furthermore, the N terminus de‐oligomerized the 2 : 2 complex of core‐cGAS and dsDNA into a 1 : 1 complex, suggesting that the N terminus enhanced the activity of core‐cGAS by facilitating formation of a monomeric complex of cGAS and DNA. Abstract :